2015
DOI: 10.1007/s10495-015-1138-9
|View full text |Cite
|
Sign up to set email alerts
|

Thymosin alpha 1 suppresses proliferation and induces apoptosis in breast cancer cells through PTEN-mediated inhibition of PI3K/Akt/mTOR signaling pathway

Abstract: Thymosin alpha 1 (Tα1), an immunoactive peptide, has been shown to inhibit cell proliferation and induce apoptosis in human leukemia, non-small cell lung cancer, melanoma, and other human cancers. However, the response and molecular mechanism of breast cancer cells exposed to Tα1 remain unclear. PTEN, a tumor suppressor gene, is frequently mutated in a variety of human cancers. In the present study, we aimed to investigate the biological roles of PTEN in the growth inhibition of human breast cancer cells expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 28 publications
2
39
1
Order By: Relevance
“…At the same time, the number of apoptotic cells increased by 22-fold ( Figure 4B). These results are in agreement with the findings of other authors (46,47).…”
Section: Tα-1 Does Not Alter F508del-cftr or Cacc Currents As Evidencsupporting
confidence: 94%
See 1 more Smart Citation
“…At the same time, the number of apoptotic cells increased by 22-fold ( Figure 4B). These results are in agreement with the findings of other authors (46,47).…”
Section: Tα-1 Does Not Alter F508del-cftr or Cacc Currents As Evidencsupporting
confidence: 94%
“…We then evaluated the effect of chronic treatment with Tα-1 on the proliferation and apoptosis of MCF-7 breast cancer cells. Indeed, various research groups reported that long-term treatment (72 hours) with Tα-1 (in the 150-500 μM concentration range) decreases the proliferation rate of MCF-7 and causes cell apoptosis (46,47). Therefore, we plated MCF-7 at low density on 96-well plates suitable for confocal high-content imaging and evaluated cell proliferation for 72 hours following treatment with Tα-1 (100 ng/ml) or scrambled peptide (100 ng/ml).…”
Section: Tα-1 Does Not Alter F508del-cftr or Cacc Currents As Evidencmentioning
confidence: 99%
“…But, differently, we identified that mTOR signaling, may be served as another way that mediated the role of KISS1 in cell function in ccRCC cells. Activation of the PI3K/Akt/mTOR pathway protects various cell types from apoptosis that is induced by the withdrawal of survival factors [39,40]. We found that knockdown of TP73-AS1 significantly activated mTOR signaling, whereas overexpression of TP73-AS1 induced inhibition of mTOR pathway while overexpressed KISS1 partly abolished this inhibition effects.…”
Section: Discussionmentioning
confidence: 73%
“…The control and reduction of apoptosis, the highly selective and programmed form of cell death, have been considered a fundamental strategy for evading the immune response in cancer development 26. Any part of the apoptosis pathway can be disturbed, causing endless proliferation of almost all types of cancers, including BC 27.…”
Section: Tumor-related Immune Evasionmentioning
confidence: 99%